Influence of Nutrition Knowledge on the Association between Maternal Nutrition and Birth Outcomes - Mehboob, Arshi; Sanghi, Divya (International Journal of Child Health and Nutrition, 2023)
Maternal undernutrition is a complex condition that arises from various factors, including social, cultural, psycho-social, biological, and ecological factors. The intergenerational consequences of chronic malnutrition, starting with mothers and their children, account for a significant proportion of infant deaths, cognitive disability, and reduced productivity in adulthood. Therefore, having nutritional knowledge throughout pregnancy is crucial for better risk assessment of undernutrition and healthy pregnancy outcomes. The study examined whether trimester-specific nutrition education and awareness could significantly impact the relationship between maternal nutrition and birth outcomes and found that this association was stronger in women with higher levels of nutrition knowledge. As a result, a food-based approach that is both low-cost and high-nutrition can help meet the specific nutritional requirements of pregnancy, alter certain nutrients that target fetal metabolic vulnerabilities, or enhance fetal growth and development in the migrant population. The review explores recent research and discusses how nutrition literacy and knowledge influence pregnancy and birth outcomes, providing an overview of the current understanding of maternal nutritional trimester-specific needs and highlighting areas that still require further study. The findings emphasize the importance of considering diet diversity and peer support during pregnancy, considering the impact that nutrition knowledge has on pregnancy outcomes.